Հայոց կանոնական ժողովածուն մատենագրական աղբյուրներում և հիշատակարաններում - Վարդանյան, Նարինե (Մատենադարան)
The Armenian canonical collection was formed in stages. Being composed in the 5th century, the Armenian Book of Canons was continually edited and gradually expanded in the following centuries, including new canonic groups. It has reached us in numerous editions similar to, or significantly different from, each other in structure and content. This article gives a general outline of yet unstudied evidences by the Armenian authors Hovhan Imastaser Odznets‘i (717-728), Mkhit‘ar Gosh (1120?-1213), and Hakob Amasiats‘i (18th-19th centuries), as well as by scribes in a number of manuscripts: New Julfa (Nor Jugha), 131 (1098), MM 7615 (1352), 659 (1368), 658 (1601), 837 (1627-1630) etc. It discusses their perceptions about the formation, further development, the role and significance of the Armenian canonical collection. In their works, medieval authors and scribes quoted from the Armenian canonical collection, praised it and pointed out the reasons and purposes of its formation and evolution, emphasizing its inseparable connection with other Christian canonical collections. Армянский сборник церковных канонов формировался поэтапно. Армянская "Книга канонов", составленная в V веке, впоследствии многократно редактировалась и постепенно расширялась благодаря включению в нее новых групп канонов. Она дошла до нас в многочисленных редакциях, схожих или существенно отличающихся друг от друга по структуре и по содержанию. В данной статье в общих чертах представлены неисследованные по сей день свидетельства армянских авторов (Ован Имастасер Одзнеци (717-128 гг.), Мхитар Гош (1120?-1213 гг.), Акоп Амасиаци (XVIII-XIX вв.) и писцов (Новая Джульфа, № 131 (1098 г.), MM №№ 7615 (1352 г.), 659 (1368 г.), 658 (1601 г.), 837 (1627-1630 гг.) и т.д.) о формировании и дальнейшем развитии, о роли и значении армянского канонического сборника. Средневековые авторы и писцы восхваляли армянский канонический сборник, цитировали его, указывали на причины и цели его формирования и расширения, подчеркивали его неразрывную связь с общехристианскими каноническими сборниками.
Keywords: Եկեղեցու պատմություն